Inovasi Kebijakan Pengelolaan Sampah Sistem Zero Waste di Nusa Tenggara Barat Model Pentahelix - Ilham Zitri; Yudhi Lestanata; Darmansyah Darmansyah; Amil Amil; Rizal Umami (Nakhoda: Jurnal Ilmu Pemerintahan, 2022)
This research was conducted in West Nusa Tenggara Province, aiming to find out the innovation of zero waste program policies. This study uses a descriptive method with a qualitative approach. The sources of data in this study are primary data obtained directly from the government, private sector, university, community and media. In addition, secondary data is also supported, which is data obtained from documents, publications, or literature related to Zero Waste Policy Innovations. The results of this study indicate that the zero waste program policy has generally been functioning and realized. Supporting factors in this zero waste program policy are government support for the program, adequate financial resources and the availability of human resources. While the inhibiting factor in this zero waste program policy is the lack awareness of the community in practice people tend to pay less attention to the problem of landfilling waste that occurs, especially the use of single-use materials that are very much in our environment. To overcome these obstacles, the Environment and Forestry Office of the Province of NTB took steps, namely increasing socialization and collaborating with other parties such as the private sector, media, academics and the community itself. The pentahelix model in the development of a zero waste program looks at the parameters of the involvement of various actors to work together in optimizing the zero waste program. the importance of collaboration with the Pentahelix Model, with the involvement of academia, the private sector, the community, government and the media is very important to support the zero waste program in the future, but so far this collaboration is still not optimal, measured from the interdependence between actors, constructive unification of thoughts, decisions together, and joint responsibility, only certain parties are involved in the collaboration, so it is important that there is a special agreement or regulation to regulate these components to be able to cooperate officially in seeking collaboration with the Pentahelix Model in the zero waste program.